1997
DOI: 10.1038/sj.bjp.0701426
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective efficacy of ebselen, an anti‐oxidant with anti‐inflammatory actions, in a rodent model of permanent middle cerebral artery occlusion

Abstract: 1 The aim of this study was to investigate whether delayed treatment with the anti-oxidant and antiin¯ammatory agent ebselen reduces the volume of infarction in a rodent model of permanent focal cerebral ischaemia. 2 Ebselen (10 or 30 mg kg 71 ) or vehicle was administered by gavage 30 min and 12 h after the induction of cerebral ischaemia by permanent occlusion of the left middle cerebral artery (MCA). Animals were killed 24 h following MCA occlusion, and the volumes of ischaemic damage in the ebselen and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
79
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(86 citation statements)
references
References 36 publications
4
79
0
3
Order By: Relevance
“…In rodent models of MCA-distribution ischemia, ebselen reduced ischemic damage when administered prior to ischemia (Namura et al, 2001) and was modestly protective if begun 30 min after induction of ischemia (Takasago et al, 1997). When treatment was begun at the onset of recirculation after 2-h MCA occlusion in rats, ebselen reduced early brain injury and improved neurological deficits at 24 hours (Imai et al, 2001), but this protection was not sustained at 7 days (Salom et al, 2004).…”
Section: Other Antioxidants: Tirilazad Ebselen Edaravonementioning
confidence: 99%
“…In rodent models of MCA-distribution ischemia, ebselen reduced ischemic damage when administered prior to ischemia (Namura et al, 2001) and was modestly protective if begun 30 min after induction of ischemia (Takasago et al, 1997). When treatment was begun at the onset of recirculation after 2-h MCA occlusion in rats, ebselen reduced early brain injury and improved neurological deficits at 24 hours (Imai et al, 2001), but this protection was not sustained at 7 days (Salom et al, 2004).…”
Section: Other Antioxidants: Tirilazad Ebselen Edaravonementioning
confidence: 99%
“…Most anti-oxidant and anti-inflammatory agents attenuate free radical toxicity (Takasago et al 1997) and have the ability to enhance chondrocyte proliferation and matrix secretion (Shang et al 2009;Wann et al 2010). A series of antioxidants, such as vitamin C (Tiku et al 2003), vitamin E (Bhatti et al 2013), and sodium ferulate (Shang et al 2009), have been demonstrated their chondro-protective properties, as well as potentials in reducing apoptosis and senescence.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other selenium compounds, ebselen possesses a very low toxicity because of its unique stability in structure and because its selenium moiety is not liberated during biotransformation and therefore does not enter the selenium metabolism of the organism (7)(8)(9). In more recent animal model studies, ebselen was shown to reduce oxidative stress in ischemiareperfusion in heart (10) and to have neuroprotective effects in brain (11)(12)(13)(14). More importantly, ebselen has been demonstrated to have beneficial effects in clinical trials for the treatment of patients with delayed neurological deficits after aneurysmal subarachnoid hemorrhage (15) and acute ischemic stroke (16,17).…”
mentioning
confidence: 99%